2023
DOI: 10.1590/s1677-5538.ibju.2023.9902
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and outcomes of HugoTM RAS System in robotic-assisted radical prostatectomy

Abstract: Background The results and benefits of Robotic-assisted Radical Prostatectomy (RARP) are already established in the literature. However, new robotic platforms have been released recently in the market and their outcomes are still unknown. In this scenario, our objective is to describe our experience implementing the Hugo TM RAS robot and report the clinical data of patients who underwent Robotic-assisted Radical Prostatectomy. Material and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 21 publications
2
32
0
Order By: Relevance
“…Although the experiences from the DV system could help early adaptation to the Hugo RAS system [ 22 ], surgeons still needed time to become accustomed to some different devices on the Hugo RAS system, such as hand controls and arm carts’ degrees of freedom [ 25 ]. We mentioned that the vesicourethral anastomosis time was longer in the Hugo RAS group in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Although the experiences from the DV system could help early adaptation to the Hugo RAS system [ 22 ], surgeons still needed time to become accustomed to some different devices on the Hugo RAS system, such as hand controls and arm carts’ degrees of freedom [ 25 ]. We mentioned that the vesicourethral anastomosis time was longer in the Hugo RAS group in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Still, we suggest that for the implementation of new technologies, mandatory laboratory-based training to proficiency should be considered, prioritizing patient safety over accepting such phenomena as reflective of real-life conditions. Other groups have published their very initial experience with H-RARP [15] , [16] , [17] , but only Ou et al [18] described the need to find optimization in ports’ placement and docking. The authors observed some intraoperative issues that slowed the procedure flow.…”
Section: Discussionmentioning
confidence: 99%
“…The Hugo TM RAS system has been primarily used in urological procedures such as RARPs and RAPNs [ 3 , 4 , 5 , 8 , 9 , 10 , 11 ]. These procedures involve the removal of the prostate or a portion of the kidney, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In the urological field, in which the system has been primarily used, Hugo TM RAS was employed for radical and simple prostatectomies, radical cystectomies, radical and partial nephrectomies, and pyeloplasty procedures [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. In gynecology, the system can be used for hysterectomies, myomectomies, and sacrocolpopexies [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%